Study of the influence of the weight average molecular weight of Poly(N-vinylimidazole) in corrosion protection of copper in acetate buffered media by cyclic voltammetry - Macchi, E.; Piatti, R.; Podestá, J. (Rev. Téc. Fac. Ing. Univ. Zulia, 1970)
Véase archivo PDF